2014
DOI: 10.4049/jimmunol.1302021
|View full text |Cite
|
Sign up to set email alerts
|

Slit2–Robo4 Pathway Modulates Lipopolysaccharide-Induced Endothelial Inflammation and Its Expression Is Dysregulated during Endotoxemia

Abstract: The secretory protein Slit2 and its receptors Robo1 and Robo4 are considered to regulate mobility and permeability of endothelial cells and other cell types. However, the roles of Slit2 and its two receptors in endothelial inflammatory responses remain to be clarified. Here we show that, in primary Human Umbilical Vein Endothelial Cells (HUVECs), Slit2 represses lipopolysaccharide (LPS)-induced secretion of certain inflammatory cytokines/chemokines, cell adhesion molecule ICAM-1 upregulation and monocyte adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 41 publications
8
84
0
Order By: Relevance
“…Our observations are consistent with work showing that Slit2 inhibited CXCL12-mediated adhesion of human breast cancer cells to fibronectin and collagen (15). Recently, Zhao et al (39) demonstrated that Slit2 prevented adhesion of monocytic cells to activated HUVEC by inhibiting LPS-induced upregulation of ICAM-1 in endothelial cells. It is possible that Slit2 similarly inhibits upregulation of ICAM-1 on the surface of endothelial cells exposed to TNF-a, contributing to the decreased adhesion of monocytic cells that we observed.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our observations are consistent with work showing that Slit2 inhibited CXCL12-mediated adhesion of human breast cancer cells to fibronectin and collagen (15). Recently, Zhao et al (39) demonstrated that Slit2 prevented adhesion of monocytic cells to activated HUVEC by inhibiting LPS-induced upregulation of ICAM-1 in endothelial cells. It is possible that Slit2 similarly inhibits upregulation of ICAM-1 on the surface of endothelial cells exposed to TNF-a, contributing to the decreased adhesion of monocytic cells that we observed.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study demonstrated that Robo-1 expression is downregulated in endothelial cells via targeting of miR-218 (39). Because Robo-1 is a single-pass transmembrane protein, cell surface levels could, in principle, also be determined by endocytosis and recycling back to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Further, among the seven, miR-29b, miR-101, miR-130a, and miR-362-3p have bioinformatically predicted binding sites on the 3= UTR of CXCL12 (see Tables S5 and S7 in the supplemental material). Similarly, miR- 218, an miRNA previously shown to exert anti-inflammatory effects by directly targeting Robo1 protein translation (47), showed markedly elevated expression in the THC/SIV group (8.6-fold increase) compared to the VEH/SIV (3.9-fold increase) and THConly (2.9-fold increase) groups (see Tables S1 to S3 in the supplemental material). Similar to the 30-day p.i.…”
Section: Plasma and Intestinal Viral Loads Cd4 And Cd8 T Cell Statusmentioning
confidence: 99%
“…The increased expression/ activity of Rap-1 leads to NF-κB induction, while Rap-1 depletion leads to NF-κB decreased activity as Rap-1 is also important for the phosphorylation of p65 subunit of NF-κB. Remarkably, similar to inhibiting NF-κB, knockdown of Rap-1 sensitizes some cells to apoptosis [35][36][37].…”
Section: Role Of Fibrinogenmentioning
confidence: 99%